2004
DOI: 10.1111/j.1365-2036.2004.02020.x
|View full text |Cite
|
Sign up to set email alerts
|

13C‐ethanol breath test reveals impaired alcohol metabolism in patients with Helicobacter pylori infection

Abstract: SUMMARY Background:The gastric mucosal alcohol dehydrogenase activity was reported to be reduced in subjects with Helicobacter pylori-associated chronic gastritis. However, the role of H. pylori infection in the metabolism of ingested ethanol has not been fully elucidated. Aim: To clarify whether H. pylori infection exerts any influence on the metabolism of small amounts of ethanol in humans. Subjects and methods: 13 C-ethanol (100 lL) diluted in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Evidence showed that ethanol exposure can potentiate the suppressive effects of HCV on innate immunity, which activates viral spread in the liver, and finally leads to impairments in adaptive immunity [36]. Moreover, the first‐pass metabolism of ethanol is attenuated in patients with H. pylori infection due to reduced alcohol dehydrogenase activity in the inflamed gastric mucosa [37]. However, more convincing evidence is needed to obtain more information on this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence showed that ethanol exposure can potentiate the suppressive effects of HCV on innate immunity, which activates viral spread in the liver, and finally leads to impairments in adaptive immunity [36]. Moreover, the first‐pass metabolism of ethanol is attenuated in patients with H. pylori infection due to reduced alcohol dehydrogenase activity in the inflamed gastric mucosa [37]. However, more convincing evidence is needed to obtain more information on this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Seventeen asymptomatic volunteers diagnosed as H. pylori-positive by the C 13 -urea breath test were orally administered urease-specific IgY for 4 weeks and then the breath test values were significantly decreased [13]. In a 53-year-old female administered urease-specific IgY, when combined with antacids, ameliorated gastric inflammation [14]. This article will focus on introducing the novel approaches on developing an effective, safe, and natural IgY against the H. pylori that may enable the future eradication of the organism as a significant human pathogen.…”
Section: Introductionmentioning
confidence: 99%
“…This method is accurate and reliable but has the disadvantage of being invasive. We previously reported that ethanol degradation into carbon dioxide could be evaluated by measuring 13 CO 2 content in breath samples after the oral intake of [ 13 C]‐ethanol 2 . In that study, [ 13 C]‐ethanol breath test (EBT) was performed after the oral intake of a small amount of ethanol (0.08 g) by healthy volunteers.…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that ethanol degradation into carbon dioxide could be evaluated by measuring 13 CO 2 content in breath samples after the oral intake of [ 13 C]-ethanol. 2 In that study, [ 13 C]-ethanol breath test (EBT) was performed after the oral intake of a small amount of ethanol (0.08 g) by healthy volunteers. We are now interested in investigating the metabolic response after ingestion of a large amount of ethanol (4 g).…”
Section: Introductionmentioning
confidence: 99%